Preparation method of bionic flower-shaped wood-based monatomic electrode and application of zinc-air battery

Through the preparation of bionic flower-like wood-based single-atom electrodes, the problems of slow reaction kinetics and poor exposure of active sites of rechargeable zinc-vacuum batteries were solved, and excellent electrocatalytic performance and stability of oxygen reduction reaction were achieved, which significantly improved zinc The cyclic charge and discharge performance and power density of empty batteries.

CN119297308APending Publication Date: 2025-01-10NORTHEAST FORESTRY UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411430035.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Rechargeable zinc-empty batteries have limited their development and application due to the slow kinetics of oxygen reduction reaction and oxygen precipitation reaction and poor exposure of catalyst active sites.

Method used

The preparation method of bionic flower-like wood-based single-atom electrode is adopted. Through the steps of delignification, metal solution impregnation, dimethylimidazole aqueous solution impregnation and high-temperature insulation, a three-dimensional porous carbonized wood skeleton and flower-like structure are formed, exposing more activity. site, binding to transition metal precursors to improve catalytic activity.

Benefits of technology

It has achieved excellent electrocatalytic performance and stability of oxygen reduction reaction, with 200 hours of cyclic charge and discharge performance, high specific capacity and power density, far exceeding the commercial catalyst Pt/C.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297308A_ABST
    Figure CN119297308A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bionic flower-shaped wood-based monatomic electrode and application of a zinc-air battery, and belongs to the technical field of catalysts. The invention aims to solve the problems of slow reaction kinetics and poor exposure of active sites of a catalyst of a rechargeable zinc-air battery. The method comprises the following steps: 1, delignification; 2, dipping in a metal solution; 3, dipping in a dimethylimidazole aqueous solution; and 4, heating and preserving heat. According to the application, the cathode material is used for a zinc-air battery cathode. The preparation method is used for preparation and application of the bionic flower-shaped wood-based monatomic electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts. Background Art

[0002] Rechargeable zinc-air batteries are considered to be one of the most promising batteries in the post-lithium-ion battery era due to their theoretical high energy density, low cost and abundant material sources. However, their development and practical application are limited by the slow kinetics of oxygen reduction reaction (ORR) and oxygen evolution reaction (ORR) occurring on their air diffusion cathodes and the poor exposure of catalyst active sites. Therefore, the development of efficient bifunctional catalysts with sufficient active sites is of great significance to promote the practical application of rechargeable zinc-air batteries. Summary of the invention

[0003] The present invention aims to solve the problems of slow reaction kinetics and poor exposure of catalyst active sites in rechargeable zinc-air batteries, and further provides a method for preparing a bionic flower-shaped wood-based single-atom electrode and zinc-air battery applications.

[0004] A method for preparing a bionic flower-shaped wood-based single-atom electrode is carried out according to the following steps:

[0005] 1. Delignification:

[0006] Delignifying the wood to obtain delignified wood;

[0007] 2. Metal solution impregnation:

[0008] The delignified wood is placed in a mixed solution of Co ions and Zn ions for vacuum impregnation, and then dried to obtain wood impregnated with a metal solution;

[0009] 3. Dimethylimidazole aqueous solution immersion:

[0010] The wood impregnated with the metal solution is placed in a dimethylimidazole aqueous solution for vacuum impregnation, and then dried to obtain a wood-based composite material;

[0011] 4. Heating and insulation:

[0012] Under the conditions of inert gas and temperature of 800°C to 1000°C, the wood-based composite material is kept warm for 1h to 6h, thereby completing the preparation method of the bionic flower-shaped wood-based single-atom electrode.

[0013] Zinc-air battery application: used as cathode of zinc-air battery.

[0014] The beneficial effects of the present invention are:

[0015] 1. The preparation method of the present invention makes full use of the chemical composition of wood cell walls, and simply and skillfully combines wood and transition metal precursors. The preparation process is simple, low cost, easy to obtain raw materials, low energy consumption, and can be mass-produced. At the same time, the synthesis of Co single atoms improves the problem of slow reaction kinetics.

[0016] 2. The present invention uses three-dimensional porous carbonized wood as a skeleton and forms a flower-like structure to expose more active sites. The obtained wood-based electrocatalyst has a three-dimensional porous self-supporting skeleton and active sites of a bionic flower-like structure. Due to the formation of a flower-like structure, the original cell wall structure of the wood can be modified, thereby generating more pores in the original three-dimensional pore structure, and the active sites are fully exposed to achieve the requirement of improving activity. The test results show that the bionic flower-shaped wood-based single-atom electrode prepared by the present invention has excellent ORR electrocatalytic performance (half-wave potential 0.89V) and stability (no significant decrease after stable operation for 10 hours).

[0017] 3. The bionic flower-shaped wood-based single-atom electrode prepared by the present invention can also be used as a component of a zinc-air battery, with a 200h cycle charge and discharge performance and excellent Specific capacity and 140mW / cm 2 The power density far exceeds that of commercial catalyst Pt / C. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope image of the bionic flower-shaped wood-based single-atom electrode prepared in Example 1;

[0020] Figure 2 This is a spherical aberration electron microscope image of the bionic flower-shaped wood-based single-atom electrode prepared in Example 1;

[0021] Figure 3 Synchrotron radiation images of the bionic flower-shaped wood-based single-atom electrode and common Co-based compounds prepared in Example 1;

[0022] Figure 4 is the LSV diagram of ORR of the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 under 0.1 M KOH;

[0023] Figure 5 The ORR stability test of the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 and the commercially purchased 20% Pt / C under 0.1 M KOH;

[0024] Figure 6 The OER and ORR cycle charge-discharge performance test diagram of a zinc-air battery assembled using the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 and a commercial 20% Pt / C and RuO2 mixture;

[0025] Figure 7 This is a graph showing the ORR specific capacity performance of a zinc-air battery assembled using the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 and 20% Pt / C;

[0026] Figure 8 This is a performance diagram of the ORR power density of a zinc-air battery assembled using the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 and 20% Pt / C. DETAILED DESCRIPTION

[0027] Specific implementation method 1: This implementation method is a method for preparing a bionic flower-shaped wood-based single-atom electrode, which is carried out according to the following steps:

[0028] 1. Delignification:

[0029] Delignifying the wood to obtain delignified wood;

[0030] 2. Metal solution impregnation:

[0031] The delignified wood is placed in a mixed solution of Co ions and Zn ions for vacuum impregnation, and then dried to obtain the wood impregnated with the metal solution;

[0032] 3. Dimethylimidazole aqueous solution immersion:

[0033] The wood impregnated with the metal solution is placed in a dimethylimidazole aqueous solution for vacuum impregnation, and then dried to obtain a wood-based composite material;

[0034] 4. Heating and insulation:

[0035] Under the conditions of inert gas and temperature of 800°C to 1000°C, the wood-based composite material is kept warm for 1h to 6h, thereby completing the preparation method of the bionic flower-shaped wood-based single-atom electrode.

[0036] The principle is as follows: Wood has a natural porous structure. After delignification, the wood cell wall will expose more hydroxyl groups, which is beneficial for the subsequent combination with the metal precursor solution. Using water as a solvent can inhibit the dissociation of dimethylimidazole during the reaction, which is beneficial for its formation of a stacked flower-like structure. After carbonization, this structure can be completely preserved and promote the formation of Co single atoms, which is beneficial for more exposure of active sites, thereby improving reaction activity and stability.

[0037] The beneficial effects of this embodiment are:

[0038] 1. The preparation method of this embodiment makes full use of the chemical composition of wood cell walls, and simply and skillfully combines wood and transition metal precursors. The preparation process is simple, low cost, easy to obtain raw materials, low energy consumption, and can be mass-produced. At the same time, the synthesis of Co single atoms improves the problem of slow reaction kinetics.

[0039] 2. This embodiment uses three-dimensional porous carbonized wood as a skeleton and forms a flower-like structure to expose more active sites. The obtained wood-based electrocatalyst has a three-dimensional porous self-supporting skeleton and active sites of a bionic flower-like structure. Due to the formation of a flower-like structure, the original cell wall structure of the wood can be modified, thereby generating more pores in the original three-dimensional pore structure, and the active sites are fully exposed to achieve the requirements of improving activity. The test results show that the bionic flower-shaped wood-based single-atom electrode prepared in this embodiment has excellent ORR electrocatalytic performance (half-wave potential 0.89V) and stability (no significant decrease after stable operation for 10 hours).

[0040] 3. The bionic flower-shaped wood-based single-atom electrode prepared in this embodiment can also be used as a component of a zinc-air battery, with a 200h cycle charge and discharge performance and excellent Specific capacity and 140mW / cm 2 The power density far exceeds that of commercial catalyst Pt / C.

[0041] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the wood material in step 1 is basswood, balsa wood, pine, fir, birch or poplar. The rest is the same as specific implementation method 1.

[0042] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that: the delignification treatment described in step 1 is to immerse the wood in a sodium hypochlorite solution, heat it at a temperature of 90°C to 120°C for 12h to 24h, and then dry it at a temperature of 30°C to 60°C for 12h to 24h to obtain delignified wood. The rest is the same as specific embodiment 1 or 2.

[0043] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the mass percentage of the sodium hypochlorite solution is 3% to 6%, and the pH is 4.1 to 4.6. Other aspects are the same as specific embodiments 1 to 3.

[0044] The mass percentage of the sodium hypochlorite solution described in this specific embodiment is 3% to 6%. When the concentration of sodium hypochlorite is too low, the lignin on the wood cell wall cannot be fully removed, which is not conducive to the subsequent binding of metal ions; when the concentration of sodium hypochlorite is too high, it will cause great damage to the structure of the wood and affect the hierarchical pore structure of the wood.

[0045] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that: the mixed solution of Co ions and Zn ions described in step 2 is obtained by adding Co source and Zn source into water and mixing them evenly; the concentration of Co ions in the mixed solution of Co ions and Zn ions is 0.5mmol / mL to 5mmol / mL, and the concentration of Zn ions is 2mmol / mL to 20mmol / mL. Others are the same as specific embodiments 1 to 4.

[0046] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that the Co source is cobalt nitrate and the Zn source is zinc acetate. The rest is the same as specific embodiments 1 to 5.

[0047] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: the vacuum impregnation described in step 2 and step 3 is specifically carried out at room temperature and a pressure of 0MPa to -0.1MPa for 1h to 24h; the drying described in step 2 and step 3 is specifically carried out at a temperature of 10°C to 103°C for 1h to 24h. The rest is the same as specific embodiments 1 to 6.

[0048] Specific embodiment 8: This embodiment is different from specific embodiments 1 to 7 in that the concentration of the dimethylimidazole aqueous solution in step 3 is 20 mmol / mL to 24 mmol / mL. The rest is the same as specific embodiments 1 to 7.

[0049] The concentration of the dimethylimidazole aqueous solution described in this specific embodiment is 20mmol / mL to 24mmol / mL. When the concentration of dimethylimidazole is too low, the flower shape cannot be formed well and the effect of exposing more active sites cannot be achieved. When the concentration of dimethylimidazole is too high, the flower shape will accumulate excessively, hindering the exposure of active sites.

[0050] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 4, the wood-based composite material is heated to 800° C. to 1000° C. at a heating rate of 3° C. / min to 10° C. / min. The rest is the same as specific embodiments 1 to 8.

[0051] Specific implementation method ten: This implementation method is a zinc-air battery application of a bionic flower-shaped wood-based single-atom electrode, which is used as the cathode of the zinc-air battery.

[0052] The following examples are used to verify the beneficial effects of the present invention:

[0053] Embodiment 1:

[0054] A method for preparing a bionic flower-shaped wood-based single-atom electrode is carried out according to the following steps:

[0055] 1. Delignification:

[0056] The wood is immersed in a sodium hypochlorite solution, heated at 90°C for 24 hours, and then dried at 60°C for 12 hours to obtain delignified wood;

[0057] The mass percentage of the sodium hypochlorite solution is 3%, and the pH value is 4.3;

[0058] 2. Metal solution impregnation:

[0059] The delignified wood is placed in a mixed solution of Co ions and Zn ions, and vacuum impregnated for 24 hours at room temperature and a pressure of -0.1 MPa, and then dried for 12 hours at a temperature of 60°C to obtain the wood impregnated with the metal solution;

[0060] 3. Dimethylimidazole aqueous solution immersion:

[0061] The wood impregnated with the metal solution is placed in a dimethyl imidazole aqueous solution, vacuum impregnated for 24 hours at room temperature and a pressure of -0.1 MPa, and then dried for 12 hours at a temperature of 60°C to obtain a wood-based composite material;

[0062] The concentration of the dimethylimidazole aqueous solution is 24 mmol / mL;

[0063] 4. Heating and insulation:

[0064] In a nitrogen atmosphere, the wood-based composite material was heated to 900°C at a heating rate of 5°C / min, and the wood-based composite material was kept warm for 3 hours in a nitrogen atmosphere at 900°C to obtain a bionic flower-shaped wood-based single-atom electrode.

[0065] The wood described in step 1 is basswood with a size of 2 cm×2 cm×2 mm (length×width×height), and is cleaned with ethanol;

[0066] The mixed solution of Co ions and Zn ions described in step 2 is specifically prepared by adding a Co source and a Zn source into water and mixing them evenly; the concentration of Co ions in the mixed solution of Co ions and Zn ions is 0.5 mmol / mL, and the concentration of Zn ions is 2 mmol / mL; the Co source is cobalt nitrate, and the Zn source is zinc acetate.

[0067] Embodiment 2: This embodiment is different from Embodiment 1 in that: the mass percentage of the sodium hypochlorite solution described in step 1 is 6%, and the pH is 4.3; the concentration of Co ions in the mixed solution of Co ions and Zn ions described in step 2 is 5 mmol / mL, and the concentration of Zn ions is 20 mmol / mL. Others are the same as Embodiment 1.

[0068] The bionic flower-shaped wood-based single-atom electrode prepared in Example 1 was cut and its morphology was observed using a high-resolution scanning electron microscope. Figure 1 This is a scanning electron microscope image of the bionic flower-shaped wood-based single-atom electrode prepared in Example 1; as can be seen from the figure, the method of the example can effectively modify the cell wall of wood to form a flower-like structure.

[0069] Figure 2 This is a spherical aberration electron microscope image of the bionic flower-shaped wood-based single-atom electrode prepared in Example 1; as can be seen from the image, significant single-atom formation can be observed.

[0070] Figure 3 Synchrotron radiation images of the bionic flower-shaped wood-based single-atom electrode and common Co-based compounds prepared in Example 1; as can be seen from the figure, by comparing with common Co-based compounds, the bionic flower-shaped wood-based single-atom electrode has no obvious Co-Co bond formation, indicating that a single atom is formed.

[0071] The bionic flower-shaped wood-based single-atom electrode prepared in Example 1 was directly used as a working electrode and immersed in a 0.1 M KOH solution to perform linear sweep voltammetry test and IT test of ORR to characterize its catalytic activity. Figure 4 and Figure 5 shown.

[0072] Figure 4 This is the LSV diagram of the ORR of the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 under 0.1M KOH; it can be seen from the figure that the half-wave potential of the electrode is 0.89V.

[0073] Figure 5 The figure shows the ORR stability test of the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 and the commercially purchased 20% Pt / C under 0.1 M KOH. As can be seen from the figure, during the chronoamperometric test, the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 ran stably for 10 hours without obvious decline.

[0074] The zinc-air battery was assembled, specifically, assembled as follows: the bionic flower-shaped wood-based single-atom electrode prepared in Example 1, a commercial 20% Pt / C and RuO2 mixture (mass ratio of 1:1) or 20% Pt / C was used as an air diffusion cathode, and a commercial zinc sheet was used as an anode, and the electrolyte was a mixed solution of KOH and 0.2M (CH3COO)2Zn, and the concentration of KOH in the electrolyte was 6M, and the concentration of (CH3COO)2Zn was 0.2M; after assembly, a cyclic charge and discharge performance test, a specific capacity test, and a power density test were performed, as shown in FIG. Figures 6 to 8 shown.

[0075] Figure 6The OER and ORR cycle charge and discharge performance test diagram of the zinc-air battery assembled using the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 and a commercial 20% Pt / C and RuO2 mixture; as can be seen from the figure, compared with the zinc-air battery assembled using a commercial Pt / C and RuO2 mixture as an air diffusion cathode, the bionic flower-shaped wood-based single-atom electrode can operate stably for 200 hours.

[0076] Figure 7 The ORR specific capacity performance diagram of the zinc-air battery assembled using the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 and 20% Pt / C; as can be seen from the figure, compared with commercial Pt / C, the specific capacity of the bionic flower-shaped wood-based electrode is

[0077] Figure 8 The ORR power density performance diagram of the zinc-air battery assembled using the bionic flower-shaped wood-based single-atom electrode prepared in Example 1 and 20% Pt / C; as can be seen from the figure, compared with commercial Pt / C, the power density of the bionic flower-shaped wood-based electrode is 140mW / cm 2 .

Claims

1. A method for preparing a bionic flower-shaped wood-based single-atom electrode, characterized in that It is carried out in the following steps:

1. Delignification: Delignifying the wood to obtain delignified wood; 2. Metal solution impregnation: The delignified wood is placed in a mixed solution of Co ions and Zn ions for vacuum impregnation, and then dried to obtain wood impregnated with a metal solution; 3. Dimethylimidazole aqueous solution immersion: The wood impregnated with the metal solution is placed in a dimethylimidazole aqueous solution for vacuum impregnation, and then dried to obtain a wood-based composite material; 4. Heating and insulation: Under the conditions of inert gas and temperature of 800°C to 1000°C, the wood-based composite material is kept warm for 1h to 6h to complete the preparation method of the bionic flower-shaped wood-based single-atom electrode.

2. The method for preparing a bionic flower-shaped wood-based single-atom electrode according to claim 1, characterized in that The wood described in step 1 is basswood, balsa wood, pine, fir, birch or poplar.

3. The method for preparing a bionic flower-shaped wood-based single-atom electrode according to claim 1, characterized in that The delignification treatment described in step 1 is specifically to immerse the wood in a sodium hypochlorite solution, heat it at a temperature of 90°C to 120°C for 12h to 24h, and then dry it at a temperature of 30°C to 60°C for 12h to 24h to obtain delignified wood.

4. The method for preparing a bionic flower-shaped wood-based single-atom electrode according to claim 3, characterized in that The mass percentage of the sodium hypochlorite solution is 3% to 6%, and the pH value is 4.1 to 4.

6.

5. The method for preparing a bionic flower-shaped wood-based single-atom electrode according to claim 1, characterized in that The mixed solution of Co ions and Zn ions described in step 2 is specifically obtained by adding a Co source and a Zn source into water and mixing them evenly; the concentration of Co ions in the mixed solution of Co ions and Zn ions is 0.5mmol / mL to 5mmol / mL, and the concentration of Zn ions is 2mmol / mL to 20mmol / mL.

6. The method for preparing a bionic flower-shaped wood-based single-atom electrode according to claim 5, characterized in that The Co source is cobalt nitrate, and the Zn source is zinc acetate.

7. The method for preparing a bionic flower-shaped wood-based single-atom electrode according to claim 1, characterized in that The vacuum impregnation described in step 2 and step 3 is specifically carried out at room temperature and a pressure of 0MPa to -0.1MPa for 1h to 24h; the drying described in step 2 and step 3 is specifically carried out at a temperature of 10°C to 103°C for 1h to 24h.

8. The method for preparing a bionic flower-shaped wood-based single-atom electrode according to claim 1, characterized in that The concentration of the dimethylimidazole aqueous solution described in step 3 is 20 mmol / mL to 24 mmol / mL.

9. The method for preparing a bionic flower-shaped wood-based single-atom electrode according to claim 1, characterized in that In step 4, the wood-based composite material is heated to 800° C. to 1000° C. at a heating rate of 3° C. / min to 10° C. / min.

10. Application of a zinc-air battery comprising a bionic flower-shaped wood-based single-atom electrode as prepared in claim 1, characterized in that It is used in zinc-air battery cathodes.